AIDS in the Twenty-First Century - Barnett, T. author. aut Link
XII, 416 p. 19 illus.
Keywords: Essential reading for social and medical scientists and all those interested in infectious diseases and public health, AIDS and the Twenty-First Century examines the social and economic origins and impacts of the HIV/AIDS epidemic. HIV/AIDS is not only a medical problem. It is an indication of the scale of the global crisis in public health. Accessibly written, this book is necessary reading for policymakers, students and all those who are concerned about the relationship between poverty, inequality and infectious diseases.